UNVEILING BARRIERS TO EXPORT AND INTERNATIONALIZATION IN AGRO-FOOD SMES: INSIGHTS FROM A BIBLIOMETRIC PERSPECTIVE - Razali , Siti Nor Diana; Raja Yusof , Raja Nerina; Mahomed , Anuar Shah Bali; Hamid , Mass Hareeza Ali (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The growing importance of Small and Medium-sized Enterprises (SMEs) in the agro-food sector highlights the need to understand export barriers that hinder their internationalization and global competitiveness. Despite their significant contribution to employment, food security, and national economies, agro-food SMEs face persistent constraints both internally and externally, limiting their export performance. To map and synthesize the intellectual landscape of this research domain, this study employs a bibliometric approach. It systematically analyses the scientific literature on export barriers in agro-food SMEs using data collected from the Scopus database. An advanced search strategy with keywords such as “export,” “export barriers,” “export performance,” “internal barriers,” “external barriers,” “agro-food,” and “SMEs” yielded a final dataset of 1,217 documents published between 2010 and 2025. The data were refined and harmonized using OpenRefine, and descriptive statistics and graphical trends were generated with the Scopus Analyzer. VOSviewer software was then applied to visualize networks of co-authorship, keyword co-occurrence, and country collaborations. The analysis reveals a notable growth in scholarly attention to agro-food export barriers, with a consistent rise in publications after 2015. Developed economies such as the United States, China, and the United Kingdom have dominated contributions. Co-occurrence mapping highlights recurring themes around financial limitations, institutional barriers, market entry challenges, and managerial capabilities, reflecting a strong theoretical anchoring in the Resource-Based View, Institution-Based View, and Network perspectives. These findings not only trace the evolution of the field but also uncover gaps in emerging markets and digital supply chain enablers, signaling directions for future research. Overall, this study enriches the understanding of export barriers in agro-food SMEs by offering a comprehensive bibliometric perspective that integrates methodological rigor, numerical insights, and conceptual contributions.